Development of self-assembled supramolecular dendritic DNA hydrogel for 3D cell culture platform - Liyarita, Bella Rosa (Nanyang Technological University, 2022)
DNA is gaining favourable attention as the versatile building block material for the hydrogel formation due to its unique properties such as sequence programmability, multifunctional tunability, precise recognition, structural rigidity, and biocompatibility. The DNA hydrogel self-assembly is formed purely by the supramolecular interaction between the complementary DNA base pairs which results to the dynamic interaction in the hydrogel and confers to the thixotropic properties and designable responsiveness of the hydrogel. Thus, allowing the DNA building block as the competitive alternative in formation of hydrogel with tailored function and precise molecular structure design. By taking advantage of these features, DNA hydrogels have been developed as the platform for 3D cell culture and bioprinting. However, some challenges still remain such as complex DNA building block design to load functionalities into the hydrogel and the low mechanical strength of the pure DNA hydrogel. In this thesis, we focus on the development of the self-assembled dendritic DNA hydrogel design to offer tailored biofunctionality and enhanced mechanical property to suit the different needs of in vitro 3D cell culture platform.